2014
DOI: 10.3168/jds.2014-8214
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectrometry of milk as a predictor of energy intake and efficiency in lactating dairy cows

Abstract: Interest is increasing in the feed intake complex of individual dairy cows, both for management and animal breeding. However, energy intake data on an individual-cow basis are not routinely available. The objective of the present study was to quantify the ability of routinely undertaken mid-infrared (MIR) spectroscopy analysis of individual cow milk samples to predict individual cow energy intake and efficiency. Feed efficiency in the present study was described by residual feed intake (RFI), which is the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 29 publications
3
97
1
1
Order By: Relevance
“…This hypothesis was based on the documented ability of milk MIR to predict EB and BCS change (McParland et al, , 2014. Research (Beam and Butler, 1999) has shown that measures such as EB, which can be predicted from milk MIR (McParland et al, 2014), affect the postpartum interval to return to cyclicity but not subsequent conception rates once the cow is cycling.…”
Section: Predictive Ability Of Conceptionmentioning
confidence: 99%
“…This hypothesis was based on the documented ability of milk MIR to predict EB and BCS change (McParland et al, , 2014. Research (Beam and Butler, 1999) has shown that measures such as EB, which can be predicted from milk MIR (McParland et al, 2014), affect the postpartum interval to return to cyclicity but not subsequent conception rates once the cow is cycling.…”
Section: Predictive Ability Of Conceptionmentioning
confidence: 99%
“…The REI definition in the present study included an interaction between BW 0.75 and BCS, which is similar to Veerkamp et al (1995), Vallimont et al (2011), andMcParland et al (2014). This term was, however, not included in other REI definitions (e.g., Coleman et al, 2010;Pryce et al, 2014).…”
Section: Residual Traitsmentioning
confidence: 99%
“…Feed conversion ratio and feed conversion efficiency are the traditional measures of feed efficiency in growing and lactating animals, respectively. Residual feed intake, used predominately in growing animals as a measure of feed efficiency (Berry and Crowley, 2013), is now also being used in lactating dairy cow populations (Coleman et al, 2010;McParland et al, 2014;Pryce 469 et al, 2014). The definition of residual energy intake (REI) in lactating cows does, however, differ among studies (Coleman et al, 2010;McParland et al, 2014;Pryce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dehareng et al (2012) have shown that enteric methane was better predicted when directly working with FT-MIR spectra than the results based on fatty acid predictions. Also recently, the FT-MIR spectrum of milk was shown to be a good indicator of body energy status , energy intake and efficiency (McParland et al, 2014), and fertility diagnosis (Laine et al, 2013) in dairy cattle.…”
Section: Introductionmentioning
confidence: 98%